DISTRIBUSI SPASIAL HIV DAN FAKTOR LINGKUNGAN: STUDI TERHADAP KEPADATAN PENDUDUK, SANITASI LAYAK, DAN INFRASTRUKTUR KESEHATAN DI PROVINSI SUMATERA UTARA - Pangaribuan, Rapael Septian; Sembiring, Ario Agantha; Perangin-angin, Zepanya Imanuel; Gulo, Ifin Niat Hati; Girsang, Vierto Irennius (PRIMA WIYATA HEALTH, 2025)
Background: The number of HIV/AIDS cases in North Sumatra Province has shown a consistent increase in recent years. While urban density is often associated with higher transmission rates, the spatial distribution and environmental determinants of HIV in this region remain underexplored. Objectives: This study aimed to analyze the spatial distribution of HIV cases in North Sumatra Province and examine their association with population density, access to proper sanitation, and the availability of healthcare facilities. Methods: A quantitative ecological design was employed, utilizing secondary data from the Central Bureau of Statistics of North Sumatra for the years 2022 and 2023. Descriptive analysis and thematic mapping were used to visualize the relationships among HIV cases, population density, sanitation access, and the number of healthcare facilities across districts. Results: Medan City recorded the highest number of HIV cases in both 2022 (1,200 cases) and 2023 (1,800 cases). However, HIV cases were also found in districts with low population density and limited infrastructure, such as Padangsidimpuan and Pakpak Bharat. The findings suggest that while urban areas have more reported cases, behavioral and awareness factors may contribute more significantly to transmission than geographic or environmental factors alone. Conclusion: The spatial distribution of HIV in North Sumatra Province is not solely influenced by population density, sanitation access, or the number of healthcare facilities. Individual behaviors, limited health literacy, and inadequate early detection mechanisms play a dominant role in the spread of HIV. Public health interventions must therefore prioritize behavioral education and equitable access to healthcare in both urban and rural regions.